Mr. Pearce's General Equilibrium Model - Ozga, S. A. (Review of Economic Studies, 1955)
Journal Article Mr. Pearce's General Equilibrium Model Get access S. A. Ozga S. A. Ozga London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 23, Issue 2, 1955, Pages 145–152, https://doi.org/10.2307/2296298 Published: 01 January 1955